2009
DOI: 10.1186/1753-6561-3-s7-s3
|View full text |Cite
|
Sign up to set email alerts
|

Genetics Analysis Workshop 16 Problem 2: the Framingham Heart Study data

Abstract: Genetic Analysis Workshop 16 (GAW16) Problem 2 presented data from the Framingham Heart Study (FHS), an observational, prospective study of risk factors for cardiovascular disease begun in 1948. Data have been collected in three generations of family participants in the study and the data presented for GAW16 included phenotype data from all three generations, with four examinations of data collected repeatedly for the first two generations. The trait data consisted of information on blood pressure, hypertensio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
57
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(57 citation statements)
references
References 6 publications
(6 reference statements)
0
57
0
Order By: Relevance
“…Data were drawn from the Framingham Heart Study original (FHS) and offspring (FHSO) cohorts (Cupples, Heard‐Costa, Lee & Atwood, 2009), the Cardiovascular Health Study (CHS) (Fried et al., 1991), the Health and Retirement Study (HRS) (Juster & Suzman, 1995), and the NIA Late‐Onset Alzheimer Disease Family Study (LOADFS) (Lee, Cheng, Graff‐Radford, Foroud & Mayeux, 2008) for individuals who identified themselves as of Caucasian ancestry. The LOADFS was designed to ascertain dementias of Alzheimer type in the elderly and recruited cases and controls.…”
Section: Methodsmentioning
confidence: 99%
“…Data were drawn from the Framingham Heart Study original (FHS) and offspring (FHSO) cohorts (Cupples, Heard‐Costa, Lee & Atwood, 2009), the Cardiovascular Health Study (CHS) (Fried et al., 1991), the Health and Retirement Study (HRS) (Juster & Suzman, 1995), and the NIA Late‐Onset Alzheimer Disease Family Study (LOADFS) (Lee, Cheng, Graff‐Radford, Foroud & Mayeux, 2008) for individuals who identified themselves as of Caucasian ancestry. The LOADFS was designed to ascertain dementias of Alzheimer type in the elderly and recruited cases and controls.…”
Section: Methodsmentioning
confidence: 99%
“…Unlike other simulation approaches that evolve population chromosomes (Peng and Amos 2010;Yuan et al 2011), our approach uses directly an initial set of real haplotypes from a population with significant structure and/or LD. For this purpose we used data on 1917 male X chromosomes from the Framingham Heart Study (FHS) data (Cupples et al 2009), chosen so that there were no reported relationships among them. Availability of this good-sized naturally phased chromosome eliminated the need for statistical phasing.…”
Section: Data Simulationmentioning
confidence: 99%
“…We analysed independent individuals from the KORA S3/F3 and KORA S4/F4 cohorts 30,36 (from the KORA study, http://www.helmholtz-muenchen.de/en/ kora), and from the Framingham Heart Study Offspring cohort (FHS-Off) 37 (Genetic Analysis Workshop 16 Framingham data, accession number phs000128.v1.p1 from the Database of Genotypes and Phenotypes (dbGaP), http://www.ncbi.nlm.nih.gov/gap). Data were retrieved and analysed in compliance with the Declaration of Helsinki.…”
Section: Materials and Methods Samplesmentioning
confidence: 99%